Is English a Killer Language or an International Auxiliary? Its Use and Function in a Globalised World - Ceramella, Nick (International Journal of Language, Translation and Intercultural Communication, 2012)
In the Introduction to this article, I deal with the importance of speaking one’s own language as a way to assert one’s identity. Then I pass on to the evolution of the English language from its start as Old English, spoken by only a few thousand Angles and Saxons. I remark how, at fi rst, it was contaminated by thousands of Latin, French and Scandinavian words, of which contemporary English still bears many clear traces, but nobody has ever thought that English was ever in danger of disappearing. By contrast, in the long run, it became the mother tongue of the speakers in comparatively newly founded countries, such as the USA, Australia, and New Zealand, and owing to the spread of the British Empire, it has dramatically increased its appeal becoming the most spoken and infl uential language in the world. Thus, according to some linguists, it has led several languages virtually to the verge of disappearance. Therefore, I argue whether English has really vampirised them, or has simply contributed to make people understand each other, sometimes even in the same country where lots of diff erent tongues are spoken (e.g. Nigeria). It is self-evident that English has gradually been taking the role of a common unifying factor in our globalised world. In this view, I envisage a scenario where English may even become the offi cial l anguage o f the E U with the c ontributions & coming, though in varying doses, from all the speakers of the other EU languages.